P147 IMPLEMENTATION OF A NEW ORAL CONTRAST AGENT FOR CT AND MR ENTEROGRAPHY IN PEDIATRIC IBD CLINICAL PRACTICE: IMPACT ON TOLERABILITY, DISTENSION, IMAGE QUALITY AND DIAGNOSTIC CONFIDENCE. (18th January 2018) - Haas, Leonard A; Iyer, Veena R; Thomas, Kristen B; Bartlett, David J; Fletcher, Joel G; Tung, Jeanne; Fidler, Jeff; Kolbe, Amy B
Abstract: Background: To evaluate the ability of pediatric patients with suspected IBD to ingest a new oral contrast agent at CT or MR enterography (CTE/MRE) and to determine the impact on small bowel (SB) distension and diagnostic confidence. Methods: For this retrospective review, pediatric patients with suspected IBD undergoing CTE/MRE from January 2014 to June 2016, ingested either conventional low-concentration barium suspension (LCBS) or a new flavored beverage containing sorbitol and mannitol (FB). The type of oral contrast, need for nasogastric tube (NGT) administration, amount ingested, emesis, distal extent of contrast within the SB, degree of SB distention, terminal ileum (TI) transverse dimension, and diagnostic confidence in presence or absence of TI disease were assessed. Studies were blindly reviewed by three abdominal radiologists. Results: 504 patients (314 female; median age 13.5 years) had 591 CTE/MREs; 316 scans performed with LCBS and 275 with FB. Most children consumed the entire amount (LCBS 97%; FB 97%). 7% of LCBS exams required NGT (23/316), compared to 1% with FB (3/275; p<0.0003). Qualitative and quantitative results are shown in Table 1. There was no significant difference in measures of small bowel distention or distal extent (p > 0.07), except for the distension of the mid-ileum (FB>LCBS; p=0.02). Diagnostic confidence was nearly identical (p=0.94). FB exams demonstrated a slight but significant increase in distal extent of contrast luminal distension (p=0.03). The LCBS group had more episodes of emesis, although not statistically significant (p=0.13). Conclusions: A new oral contrast agent FB performed equivalently to conventional LCBS in pediatric patients with suspected IBD for all measures of small bowel distention, performed slightly better for mid-ileal distention and distal extent of contrast luminal distention, and was associated with significantly decreased need for onerous NGT administration (p=0.0003).